Boundary-value problems for a nonlinear parabolic equation with Lévy Laplacian resolved with respect to the derivative - Kovtun, I. I.; Feller, M. N. (Ukrains’kyi Matematychnyi Zhurnal, 2010)
We present the solutions of boundary-value and initial boundary-value problems for a nonlinear parabolic equation with Lévy Laplacian $∆_L$ resolved with respect to the derivative$$\frac{∂U(t,x)}{∂t}=f(U(t,x),Δ_LU(t,x))$$in fundamental domains of a Hilbert space.